PROKRASTINASI PADA PESERTA PENDIDIKAN KARAKTER DAN FAKTOR-FAKTOR PENYEBABNYA - Arundati Shinta dan Singgih Purwanto (LPPM Universitas Proklamasi 45, 2015)
Procrastination is a kind of failure on self-regulation to accomplish a task based on a voluntary intention. Although he or she understands the consequence, this kind of behavior occurs repeatedly. This kind of harmful behavior frequently occurred among the IAYP (International Award for Young People) participants. IAYP is a kind of character building program. The program requires participants to accomplish three activities i.e. sport, skill, and community service once per week during 24 weeks (either for bronze and silver level). This program trained participant to have internal motivation. Hence, the objective of this research is to discuss the causal factors of the procrastinate behavior on one IAYP participant. Currently he is still at the bronze level and frequently performs procrastination of those three activities. This preliminary research revealed that the external and internal factors are the reason for procrastination. The interesting external factor which contributes is the subject's perception about the IAYP leader. The leader is perceived as not having empathy for participant's inability to conform the IAYP schedule. The subject is likely to ask an excuse for being procrastinate. This result mirrored that the fundamental reason for being procrastination is subject’s inability to build internal motivation (internal factor).